Synthesis of Analogues of Gingerol and Shogaol, the Active Pungent Principles from the Rhizomes of Zingiber officinale and Evaluation of Their Anti-Platelet Aggregation Effects - Hung-Cheng Shih (International Journal of Molecular Sciences, 2014)
The present study was aimed at discovering novel biologically active compounds based on the skeletons of gingerol and shogaol, the pungent principles from the rhizomes of Zingiber officinale. Therefore, eight groups of analogues were synthesized and examined for their inhibitory activities of platelet aggregation induced by arachidonic acid, collagen, platelet activating factor, and thrombin. Among the tested compounds, [6]-paradol (5b) exhibited the most significant anti-platelet aggregation activity. It was the most potent candidate, which could be used in further investigation to explore new drug leads.